Relations of the use of out-of-school suspensions in U.S. public pre-kindergarten programs to neighborhood opportunity - Fabes, Richard A.; Shen, Zuchao; Catherine, Evandra; McDonald, Ashley; Low, Sabina; Xie, Fuzhe (Frontiers in Developmental Psychology, 2024)
A key goal of the U.S. and its citizens is to promote positive development for young children and their families, particularly those who are marginalized and vulnerable. However, suspending young children from pre-kindergarten (Pre-K) undermines this goal. The primary purpose of the present research was to document the extent to which young children are suspended from Pre-K and how these suspensions are related to the quality of the Pre-K neighborhood. To do this, we used national data from the 26,122 public Pre-K schools in the 2017-2018 Civil Rights Data Collection and examined how the quality of neighborhood resources related to the use of out-of-school suspensions (OSS) for all children, as well as separately for Black and white children, and male and female students. We found that children living in low-opportunity neighborhoods tended to be enrolled in U.S. Pre-K public school programs that had high rates of OSS. We also found that disparities in the rates of use of OSS were greater for Black relative to white students and male relative to female students in Pre-K schools that resided in relatively low-resourced neighborhoods. The findings highlight that one of the ways that neighborhoods influence children's health and well-being is through the disciplinary culture of its schools. The present findings also highlight that disparities in the use of OSS are tied to these neighborhood opportunities and conditions.